Influence of HBr-additives on Cu and CuBr vapor laser performances; Korus 2004; Vol. 2 - Zhdaneev O. V.; Evtushenko G. S. Gennady Sergeevich; Shiyanov D. V. Dmitry Valeryevich; Sukhanov V. B. Viktor Borisovich (2004, 2004)
The influence of small active HBr-additives on Cu and CuBr-vapor laser performances are studied. The experiments has shown that introducing of HBr addition into the CuBr laser active medium results in the increase of radiation power and efficiency, comparable to the increase, obtained with the present gas discharge tube in CuBr-H2 laser. The analysis of electrical characteristics (amplitude, pumping pulse duration) at equal excitation conditions of CuBr+HBr and CuBr+H2 lasers has also shown their complete identity. The results of modeling of copper vapor laser active medium kinetics with HBr and Br2 additions are also adduced in the work. The main reasons which limit the output parameters of the lasers are discussed.